2022
DOI: 10.1088/1361-6528/ac8997
|View full text |Cite
|
Sign up to set email alerts
|

Transfer-free, scalable vertical heterostructure FET on MoS2/WS2 continuous films

Abstract: Taking into account the novel layered structure and unusual electronic properties of MoS2 and WS2 on the side the lack of dangling bonds between these two components and donor-acceptor linkage effects, growth of the MoS2/WS2 vertical heterojunction film on the amorphous SiO2/Si substrate have created high demand. In this study, we reported the continuous, scalable, and vertical MoS2/WS2 heterostructure film by using a sputtering without a transfer step. The WS2 film was continuously grown on MoS2 and eventuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…61 and in more recent references. 27,[62][63][64][65][66][67][68] We also stress that the absolute photocurrent and photovoltage values which have been measured in our proofof-concept TMD heterojunction are far too low for any realistic electro-optical photoconversion application. This limitation is primarily due to the very high series resistance of the graphene bilayer back contact, in the range of 20 kΩ (more details in ESI † section S4).…”
Section: Rsc Applied Interfaces Papermentioning
confidence: 88%
“…61 and in more recent references. 27,[62][63][64][65][66][67][68] We also stress that the absolute photocurrent and photovoltage values which have been measured in our proofof-concept TMD heterojunction are far too low for any realistic electro-optical photoconversion application. This limitation is primarily due to the very high series resistance of the graphene bilayer back contact, in the range of 20 kΩ (more details in ESI † section S4).…”
Section: Rsc Applied Interfaces Papermentioning
confidence: 88%
“…[167] Vertical van der Waals heterostructures combined with ambipolar 2D semiconductors allow for the integration of highly disparate materials with crystal lattice mismatching. [168] They have been employed in the construction of high-performance electronic and optoelectronic devices, such as ReSe 2 /MoS 2 van der Waals heterostructures, which exhibit ultra-fast and linear polarization-sensitive photodetectors, [169] vertical MoS 2 /WS 2 heterostructure with ambipolarity behavior, [170] vertical graphene/WS 2 /graphene van der Waals heterostructure with a low off-state current and a high ON/OFF ratio, exhibiting both n-type and bipolartype conduction, [171] ReSe 2 /PtSe 2 heterojunction for highperformance photodetectors, [172] WSe 2 /InSe heterostructure photodetector with ambipolar photoresponsivity, [173] and ambipolar SnO/SnS heterojunction transistors employed to build CMOS inverters. [174] Such investigations indicate that vertical heterostructures hold great potential for use in reconfigurable devices towards high-performance integrated circuits and systems.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional (2D) semiconducting materials have been studied extensively as photodetectors because of their intriguing optical properties. Among them, transition metal dichalcogenides (TMDCs) are one of the most investigated owing to their widely tunable electronic bandgap ranging from ∼few tens meV to ∼2 eV. Even though various studies have reported the wafer-scale synthesis of TMDCs for CMOS-based applications, TMDCs are vulnerable to oxidation from ambient conditions, which have impeded their use as a replacement for Si technology. In the past few years, air-stable layered materials, such as n-type bismuth oxychalcogenides (Bi 2 O 2 Se), and monoelemental materials, such as p-type tellurene, have been synthesized by chemical vapor deposition (CVD) and hydrothermal synthesis and utilized for short wavelength infrared (SWIR) photodetectors and MIR at room temperature. Since photodetectors integrated with single 2D materials in the conventional transistor configuration exhibit very low photoresponses owing to their very small absorption cross section and only the interface of the gate (G)–source (S) and gate (G)–drain (D) contributing to the photocurrent induced by electron and hole separation at the Schottky barrier, vertically stacked photoreactors have been investigated to overcome this issue by maximizing photoactive area, i.e., highly enhanced absorption cross section. Among them, a vertically stacked van der Waals heterojunction, i.e., forming a p–n junction using two different kinds of materials, or the same type of polarity with different Fermi level has been reported for a high on/off ratio, superior interface quality because of the lack of dangling bonds in the 2D materials, and bandgap engineering due to numerous selections of van der Waals materials of various bandgaps and work function for p- and n-type semiconductors. , These devices usually exhibit a photoresponse toward fast photodetectors with rise or fall times of tens of μs to ms. , Even though a very slow photoresponse with a long retention time in vertically stacked heterostructured devices using van der Waals 2D materials has been recently reported, …”
Section: Introductionmentioning
confidence: 99%